Analysing quality performance gaps between customer expectations and developers perceptions in the software industry. (1st January 2013) - Mehrez, Ahmed
The assessment of quality is pervasive but vital in organisations. It is particularly important in the design of an effective quality management system. The assessment is often considered from the perspective of fulfilling customers' requirements; however, the level of compatibility between a product or service providers' perceptions of what to deliver and the customers' desires or expectations is often uncertain. This paper describes an empirical study evaluating, within the software industry in Egypt, the extent to which differences, or 'gaps', may exist between software provider perceptions and customer expectations regarding the levels of ideal and actual degrees of performance within multiple dimensions of quality. The study involved a survey of 142 software developers and 111 software customers where gaps were found to exist across nine measured dimensions of quality. These gaps were found to be both statistically and practically significant. The existence of such quality performance gaps is often not measured. These gaps, however, must be firstly measured, and recognised, and secondly addressed within an organisation otherwise there will exist 'flaws' within the design and implementation of the organisation's quality management programme.